The influence of social support and hope on academic grit among students at Universitas Negeri Makassar - Nurfadilah Ramdani La Sunra; M. Ahkam Alwi; La Sunra La Sunra (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2026)
This study aims to examine the effects of social support and hope on academic grit among university students. The study involved 425 active students at Universitas Negeri Makassar aged 18–23 years, selected using a multistage cluster random sampling technique. Data were collected using the Academic Grit Scale, the Social Support Scale, and the Adult Dispositional Hope Scale, and were analyzed using multiple linear regression. The results indicate that social support and hope significantly influence academic grit, accounting for 44,3% of the variance (R2 = 0,443; p = 0,000). These findings suggest that higher levels of social support and hope are associated with greater academic grit among students. This study highlights the importance of strengthening both external and internal factors in fostering academic grit and may serve as a basis for developing psychological intervention programs for university students.